Skin barrier-inflammatory pathway is a driver of the psoriasis-atopic dermatitis transition - Dong, Sitan; Li, Dongmei; Shi, Dongmei (Frontiers in Medicine, 2024)
Psoriasis and atopic dermatitis (AD) areAs chronic inflammatory conditions driven by immune dysregulation influenced by both genetics and environment factors. Traditionally, psoriasis and atopic dermatitis (AD)they have traditionally been viewed asconsidered to be distinct diseases characterized by different T cell responses. Psoriasis, which is associated with type 17 helper T (Th17)-mediated inflammation, presenting presents as well-defined scaly plaques with minimal pruritus. Conversely, AD, which is primarily linked to Th2-mediated inflammation, presenting presents with poorly defined erythema, dry skin, and intense itching. However, there are instances where psoriasis and AD may overlap or transition into one another spontaneously, independent of biological agent usage. Emerging evidence suggests that defects in skin barrier-related molecules interact with the polarization of T cells polarization, which forming forms a skin barrier-inflammatory loop with them. This loop contributes to the chronicity of the primary disease or the transition between psoriasis and AD. This review was aims aimed to at elucidate elucidating the mechanisms underlying skin barrier defects in driving the overlap between psoriasis and AD. It In this review, underscores the importance of repairing the skin barrier was underscored, and emphasizes the significance of tailoring biologic treatments based on individual immune status, rather than instead of solely adhering to the treatment guidelines for AD or psoriasis was emphasized.